A systematic review of the exercise effects on burn wound healing - Niumanlan; Jingming, Yan; Hao, Qin; Farzan, Ramyar; Alizadeh Otaghvar, Hamidreza (International wound journal, 2024)
The emerging evidence has indicated the role of microRNAs (miRNA) in various physiological or pathological processes. Also, documents have suggested that exercise, by affecting miRNA regulation, may enhance burn wound healing. The current study aims to systematically review the role of exercise in regulating miRNAs related to burn wound healing to provide potential therapeutic targets. A comprehensive, systematic search was performed in different international electronic databases, such as Embase, PubMed and Google Scholar search engine, Science Direct, ProQuest and Ovid using keywords extracted from Medical Subject Headings from 2010 to September 2023. The keywords, including ‘exercise’ AND ‘burn wound’ AND ‘microRNA’ and finally, six cases were achieved. Evidence has indicated that exercise may promote the healing of burn wounds by regulating certain miRNAs. Studies have found that exercise regulates the expression of miRNAs such as mir‐155, miR‐21, let‐7a, miR‐146a, miR‐122 and mir‐210 in burn wound tissue, which regulate inflammation and angiogenesis. These findings suggest that miRNAs may play a role in the positive effect of exercise on burn wound healing. However, further research is needed to understand the mechanisms involved fully.